Factors contributing to poor service delivery in South African rural communities - Moloto, A. N.; Mkhomazi, S. S.; Worku, Z. (Annual International Conference on Public Administration and Development Alternatives, 2020)
The lives of the South Africans citizens in most rural communities are currently being impacted by the poor level of services delivery. South Africa has been a democratic country since 1994, however, after 26 years of freedom, citizens are still struggling to meet the basic needs, such as water and sanitation, transport, good roads and technological infrastructures and education. The level of service delivery in rural communities is less than compared to urban areas and furthermore, there is no sign of improvement. There is a need to improve the level of service delivery in rural areas as the pace of service delivery has been slow and poor. Though the local municipalities are mandated to provide good quality services to the rural areas, however, most municipalities also face infrastructure challenges. The paper aims to analyse the factors contributing to poor service delivery in South African rural communities.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Basic needs; Economic development; Local municipalities; Service delivery; Rural communities; Local governement - Administration